Negotiating two spaces: examining how structural policies and family politics shape the education of children - Akuffo, AG (2023)
Despite efforts by both global education regimes and states to make education access equitable for all children, underlying patterns of inequity in access to education persist. The underlying patterns of inequity in access make education access and distribution gendered, school-based, classed, and geographic or region-based. Using Ghana’s recent education policy, “the free Senior High School (SHS) policy” as an exemplar, the thesis explores the gender disparities in access to education that the national data fail to unmask in various parts of Ghana where such disparities persist, and in places where gender parity has been overachieved. Based upon one and half years of qualitative fieldwork in Ghana, which incorporated 328 interviews with policymakers, implementers, and diverse families, and over two years of desk research, this thesis addresses the question presently unresolved in the education access literature: how does the nexus of structural education policies and family politics shape upper secondary education of children in Ghana?